Preparing Students for College and Careers Theory, Measurement, and Educational Practice - McClarty, Katie Larsen; Mattern, Krista D.; Gaertner, Matthew N. (Taylor & Francis, 2018)
Preparing Students for College and Careers addresses measurement and research issues related to college and career readiness. Educational reform efforts across the United States have increasingly taken aim at measuring and improving postsecondary readiness. These initiatives include developing new content standards, redesigning assessments and performance levels, legislating new developmental education policy for colleges and universities, and highlighting gaps between graduates' skills and employers' needs. In this comprehensive book, scholarship from leading experts on each of these topics is collected for assessment professionals and for education researchers interested in this new area of focus. Cross-disciplinary chapters cover the current state of research, best practices, leading interventions, and a variety of measurement concepts, including construct definitions, assessments, performance levels, score interpretations, and test uses.